Feminization of agriculture in China?: Myths surrounding women's participation in farming - de Brauw, Alan; Li, Qiang; Liu, Chengfang; Rozelle, Scott; Zhang, Linxiu (Cambridge University Press, 2008)
The goals of this article are to help build a clear picture of the role of women in China's agriculture, to assess whether or not agricultural feminization has been occurring, and if so, to measure its impact on labour use, productivity and welfare. The article uses two high quality data sets to explore who is working on China's farms and the effects of the labour allocation decisions of rural households on labour use, productivity and welfare. It makes three main contributions. First, we establish a conceptual framework within which to define the different dimensions of agricultural feminization and its expected consequences. Second, as a contribution to the China literature and contrary to popular perceptions, we believe we have mostly debunked the myth that China's agriculture is becoming feminized; it is not. We also find that even if women were taking over farms, the consequences in China would be mostly positive – from a labour supply, productivity and income point of view. Finally, there may be some lessons for the rest of the world on what policies and institutions help make women productive when they work on and manage a nation's agricultural sector. Policies that ensure equal access to land, regulations that dictate open access to credit, and economic development strategies that encourage competitive and efficient markets all contribute to an environment in which women farmers can succeed.